Supplementary effect of K. alvarezii baesd seaweed product on milk production, its composition and organoleptic appraisal in crossbred cows - Sharma, Avinesh Sharma, Chander Datt, Jitendra Kumar, Kuldeep Dudi, Shambhvi, Veena Mani; SS Lathwal (Indian Journal of Dairy Science, 2022)
Eighteen crossbred cows were divided into 3 groups of 6 animals each based on milk yield, body weight, parity and days in milk to study the effect of supplementation of K. alvarezii based SWP on feed consumption, milk production and composition for a period of 150 days. The cows in group T1 were fed rations as per their nutrient requirements (ICAR, 2013). The cows in groups T2 and T3 were fed the similar rations as in control group (T1), however, the diets were supplemented with 1.5 and 3% of K. alvarezii based SWP (K. alvarezii powder: Gracilaria salicornia powder: K. alvarezii sap powder in 1: 1: 1 ratio) on DM basis through concentrate mixture in groups T2 and T3, respectively. Daily feed consumption, milk composition and organoleptic appraisal of milk were not influenced by SWP supplementation, however, persistency of lactation seemed to be better in group 3 supplemented with 3% SWP in the ration of crossbred cows particularly post Â 5th fortnight after start of the experiment.